Controlled vocabulary dictionary for UAV, phenotyping and image data annotation - CGIAR Platform for Big Data in Agriculture (2019)
The controlled vocabularies for UAVs, phenotyping and imagery have been developed and piloted with IRRI's drone data trials, however still further development is required for these to move to the uptake rom next users.